Green Value and Price Fairness on Young Consumers Purchase Intention of Electric Motorcycle: The Moderating Role of Environmental Knowledge - Abbada, Jihan -; Winarto, Winarto -; Ayuwardhani, Mellasanti - (Admisi dan Bisnis, 2024)
The preservation of the natural environment is an increasingly growing issue in Indonesia. The program to convert oil-fueled motorcycles to environmentally friendly electric energy has not been successful as expected.This study aims to analysis the influence of Green Perceived Value and Price Fairness on Purchase Intention of Electric Motorcycle Moderated by Environmental Knowledge. The sampling method was purposive sampling with119 university students as    respondent. Data analysis techniques used linear regression with moderated variable. Result of research, Green Perceived Value and Price Fairness with moderated by Environmental Knowledge, have a significant effect on Purchasing Intention of Electric Motorcycle. It is hope to contribution a solution to the problems, with the implementation of green perceived value, price fairness, and environmental knowledge to increase purchasing intention of electric motorcycles among young customer.